O'Brien ,Aloysius 3.Interview about the land use and farming - Shawyer; Jo (1992)
The topics concentrate on the different locations of meadows in the farm and the rotation syetem in the field. Aloysius talked about the cultivation of hay, crops and vegetables in the farm "00:00-05:00 they are looking at a map of the farm; identifying different locations on the map; the farmhouse and its history 05:00-10:00 the barn; summer houses; the use of lands in the farm; 10:00-15:00 Different use of the lands in the farm; meadows; 15:00- 20:00 pasture; crop; drains; 20:00-25:00 drains; the time in a year for different work; oats 25:00-30:00 oats and hay; the growth of crop; clover; the rotation system in the field 30:00-35:00 ploughing; the time for different work; turnips and cabbages; oats and hay 35:00-40:00 harrowing; ploughing; horse working; bush harrow 40:00-45:00 bush harrow; hay wire; top meadow 45:00-50:00 land clearing; big fire in Pippy Park; meadow and pond 50:00 -55:00 land clearing in 19th century “Irish youngsters”, the Irish immigrants; 55:00- 56:28 turnips cabbage; the rotation systems used in the field "